Diarylsulfones, a new chemical class of nonnucleoside antiviral inhibitors of human immunodeficiency virus type 1 reverse transcriptase. - McMahon, J B (1993)
A series of variously substituted diarylsulfones and related derivatives were found to prevent human immunodeficiency virus type 1 (HIV-1) replication and HIV-1-induced cell killing in vitro. One of the more potent derivatives, 2-nitrophenyl phenyl sulfone (NPPS), completely protected human CEM-SS lymphoblastoid cells from the cytopathic effects of HIV-1 in cell culture at 1 to 5 microM concentrations. HIV-1 replication, as assessed by the production of infectious virions, viral p24 antigen, and virion reverse transcriptase (RT), was inhibited by NPPS at similar concentrations. There was no evidence of direct cytotoxicity of the drug at concentrations below 100 microM. A variety of other CD4+ T-cell lines as well as cultures of peripheral blood leukocytes and monocytes were protected from HIV-1-induced cytopathicity and/or viral replication. NPPS also inhibited several distinctly different strains of HIV-1 but was ineffective against three strains of HIV-2. Biochemical studies revealed that NPPS inhibited HIV-1 RT but not HIV-2 RT. NPPS had no direct effect on HIV-1 virions, nor did it block the initial binding of HIV-1 to target cells. Time-limited treatments of cells with NPPS found that NPPS had to be present continuously in culture to provide maximum antiviral protection. In addition, HIV-1 replication in cells in which infection was already fully established or in chronically infected cells was also unaffected by NPPS. We conclude that NPPS acts in a reversible manner as a nonnucleoside HIV-1-specific RT inhibitor. Although markedly different in structure from a larger, structurally diverse group of known HIV-1-specific nonnucleoside RT inhibitors, NPPS shares several of the biological properties that characterize this emerging new pharmacologic class.